"Akcja lubelska" na Ziemi Lubuskiej w 1951 roku = "Action Lublin" in the region of Lubuska Land in 1951 - Halczak, Bohdan (Zielona Góra: Oficyna Wydawnicza Uniwersytetu Zielonogórskiego)
The exchange of territory between the Polish Republic and the Union of Soviet Socialist Republics took place in 1951. Poland gave the Soviet Union an area of 480 km square. The Soviet Union gave Poland the same territory. In the area submitted by Poland to the Soviet Union there were about 14,000 Poles. They were resettled to other areas of the Polish state. 1,306 people have been settled in the region called Lubuska Land.
Keywords: Polska; ZSRR; Ziemia Lubuska; wymiana terytorium; przesiedlenia ludności; Poland; USSR; Lubuska Land; the exchange of territories; displacement of people